2012
DOI: 10.1162/pres_a_00091
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Physics-Based Target Shooting Game to Train Amputee Users of Multijoint Upper Limb Prostheses

Abstract: For upper limb amputees, learning the control of myoelectric prostheses is difficult and challenging. Introduction of newer prostheses with multiple degrees of freedom controlled by various neural commands will make such training even more difficult. To produce smooth and human-like movements, the user must learn to produce multiple neural commands with precise amplitude and timing. To aid in training of the amputee users, we have developed a realistic and motivating virtual environment (VE) consisting of a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…So far, myogame research has not shown much empirical evidence for their benefit (see e.g. [ 1 , 3 , 4 , 6 10 ], but see [ 12 ]). The current designs therefore do not yet warrant testing for motor learning effects on patient groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, myogame research has not shown much empirical evidence for their benefit (see e.g. [ 1 , 3 , 4 , 6 10 ], but see [ 12 ]). The current designs therefore do not yet warrant testing for motor learning effects on patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…using a myogame). Many studies so far limit their research to the development of the myogame, and do not include an evaluation of training effects after using the game [ 3 , 4 ]. Studies that did include the training of the myogame often did not provide statistical support for apparent improvement in performance and, with the exception of one study [ 5 ], none have used a control group [ 6 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They either apply too much pressure and break the shell or apply too little pressure and have it slip from their grasp. Healthy humans, by contrast, do not need to pay constant visual attention (Davoodi and Loeb, 2012) during such tasks because the tactile sensors (mechanoreceptors) in their skin allow them to easily regulate the grasping force level (Ferrington et al, 1977;Dargahi and Najarian, 2004). The central nervous system (CNS) transmits proprioceptive and exteroceptive information whenever one comes into contact with an external stimulus; over time, these experiences are used to inform one's reaction to present events (Hager-Ross et al, 1996;Augurelle et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The system designed by Hargrove et al is meant to simulate an interactive task but does not actually include contact dynamics [6]. Applications of the Davoodi and Loeb environment which incorporate some form of contact dynamics have been described but user control of these has not been demonstrated [19], [20]. The interactive trans-humeral virtual prosthesis developed by Lambrecht et al [11] had four control-classes (Elbow flexion/extension, forearm supination, and hand open) under synchronous EMG control and was controllable by able-bodied subjects.…”
Section: Introductionmentioning
confidence: 99%